TECHNOLOGY OF PEER LEARNING IN THE CONDITIONS OF DIGITAL TRANSFORMATION OF HIGHER EDUCATION IN UKRAINE - Артюшина, Марина; Саркісова, Оксана (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article is devoted to the problem of ensuring the constructive interaction of the participants of the educational process, the development of their communicative skills in the conditions of online education. The purpose of the research was to determine the theoretical and applied aspects of the introduction of peering learning technology in the higher education of Ukraine in the context of its digital transformation. The research was based on the use of the following methods: theoretical analysis, comparison and generalization, as well as the method of studying pedagogical experience and activity products. In the course of the study, the expediency and importance of using peering learning technology in higher education institutions of Ukraine in the context of its digitalization was substantiated. The essence and features of peering learning technology were shown. Forms and organizational parameters of peering training methods, organizational aspects of were implementation are defined. The essence and importance of peer evaluation is revealed, the components of its design were indicated. The possibility of combining peer learning with information technologies in education was shown. The practice of using peering learning technology in foreign institutions of higher education was studied. The conditions of effectiveness and efficiency of peering training was shown. The results of the research proved the expediency of using peering learning technology in higher education institutions of Ukraine to increase the success of students and the effectiveness of learning, to ensure their constructive interaction, the formation of communication skills in the conditions of digitization of higher education and the implementation of mixed and online learning. Based on the results of the research, conclusions were formulated about the essence, features and effectiveness of the peering learning technology, as well as the expediency of its introduction into higher education in Ukraine.